Streetscapes as Surrogate Greenspaces During COVID-19? - Fischer, Leonie K.; Gopal, Divya (Frontiers in Sustainable Cities, 2021)
In 2020, the spread of COVID-19 (SARS-CoV-2) globally led to severe crisis, disruption and hardship in both private and public life. In such times of distress, access to urban greenspaces is essential for physical and mental wellbeing. However, globally implemented lockdowns deprived many people of freely visiting greenspaces. Inequality in access to urban greenspaces was apparent at global scales. Consequently, many people took to streets for outdoor activities due to its easy accessibility. We, therefore, aimed to study the usage and relevance of streetscapes for outdoor activities during a crisis. We hypothesized that streetscapes supported diverse outdoor activities, functioning as surrogate urban greenspaces. We distributed an online questionnaire to over 400 international respondents. Our results clearly showed that people used streetscapes during this period for a variety of activities, many of which were also reported as their main physical activity. Walking was the most frequent activity in streetscapes globally, and independent from sociocultural characteristics. Other activities reported such as jogging and cycling also aligned generally with main physical activities of people, but differed between countries and people’s sociocultural background. In summary, more than one third of respondents from lower-income countries reported not having had access to a greenspace, whereas 8% reported the same in high-income countries. Our results highlight the important role of streetscapes in facilitating people’s regular physical activities during the pandemic. Recognizing streetscapes as important public outdoor spaces within residential neighborhoods could help counteract the inequality in greenspace access, an issue that seems more relevant than ever before.